Alleviating malnutrition through agronomic bio-fortification using value-added fertilizers - S, Vijayakumar; M, Sivashankari; R, Gobinath; Saha, Sanjoy; G, Prabhu (Indian Farming, 2021)
In India, a significant portion of the population is suffering due to nutritional deficiency (malnutrition). The common nutritional deficiencies are vitamin A, zinc (Zn), iron (Fe), and protein. Improving the nutritional value of food is considered as the most sustainable and cost-effective approach to alleviate the malnutrition in India. Food fortification classified into 2 groups viz. bio-fortification (involvement of breeding techniques) and agronomic fortification (through the application of fertilisers). Application of value-added fertilizers such as customized, fortified and complex fertiliser is the most effective method to improve soil health through correcting the native soil nutrient deficiency. While the use of speciality fertilizers like water-soluble and liquid fertilizers are more suitable for nutritional enrichment through fertigation and foliar spray, respectively. Thus, the use of both soil and foliar fertilization using value-added fertilizers will be the most effective method for improving the nutritional quality of grain. Agronomic fortification is a short-term solution and complementary method to genetic bio-fortification which is more sustainable.